Pandoraea apista Bacteremia in a COVID-Positive Man: A Rare Coinfection Case Report from North India - Singh, Sweta; Sahu, Chinmoy; Patel, Sangram Singh; Garg, Atul; Ghoshal, Ujjala (Journal of Laboratory Physicians, 2021)
Pandoraea apista is a novel gram-negative bacillus usually isolated from respiratory specimens of cystic fibrosis patients. Few cases of bacteremia have also been reported due to this rare pathogen. Emergence of multidrug-resistant isolates of this bacillus is of grave concern. Here, we report a very interesting and unusual case of Pandoraea apista bacteremia in a coronavirus disease (COVID)–positive elderly diabetic man suffering from pneumonia. Prompt isolation and antibiotic sensitivity testing guided the patient’s treatment and yielded favorable outcome. The need of automated methods for identification and sensitivity testing limits the reporting of this rare but important pathogen in hospital settings. Detailed research work and studies are needed in this direction to better understand this pathogen and its clinical manifestations for better patient outcome.
Keywords: Pandoraea apista; bacillus; cystic fibrosis; bacteremia; COVID; pneumonia